Espionage activities in the perspective of international law - Nabih Amer (Institute Of computer Science (IOCS), 2024)
This study's overarching goals are to determine whether or whether espionage operations constitute a breach of state sovereignty, the nature and extent of such a breach, the impact on international law, and the methods used to address such disputes. Normative law, which entails investigating relevant legal concepts and statutes, is the research methodology used. The legislative method is the cornerstone of this strategy, which is based on library research that encompasses primary, secondary, and tertiary legal literature. National sovereignty and international law are both violated by espionage operations, according to the study's findings. Possible remedies to espionage in the context of diplomatic relations include designating the offender as a